Implementasi Mata Kuliah Model & Strategi Pembelajaran dalam Meningkatkan Kompetensi Pedagogi Mahasantri Ma’had ‘Aly Sa’idusshidiqiyah Jakarta - fitriani, nur (STAI Ma'had Aly Al-Hikam Malang, 2025)
The course on Models & Learning Strategies is a crucial component in the teacher education program, aimed at equipping students with the ability to design, implement, and evaluate effective learning processes. This study aims to analyze the implementation of this course in enhancing the pedagogical competence of students at Ma’had ‘Aly Sa’idusshidiqiyah Jakarta. A qualitative approach using a case study was employed, with data collected through participatory observation, interviews, and documentation. The findings indicate that the pedagogical competence of the students is good, as seen from their microteaching practice results, where the majority earned an A, with only 2 students receiving a B out of 21 students. This competence is reflected in the students' ability to understand the subject matter, plan, implement, and evaluate the learning process effectively. These findings highlight the importance of mastering models & learning strategies to enhance the practical skills of students in creating creative, interactive, and meaningful learning experiences.